Pengembangan Iot Middleware Berbasis Event-Based Dengan Protokol Komunikasi CoAP, MQTT Dan Websocket - Husnul Anwari; Eko Sakti Pramukantoro; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The condition of the Internet of Things (IoT) is currently depicted as trapped in a silo. This means that each communication between devices is limited to one domain, this is due to problems at the middleware that is used is limited to protocol data according to specific devices, known as syntactical interoperability. The solution of the problem is a multi-protocol middleware architecture that can be used by all types of devices. This research developed a midlleware to answer the challenge of syntactical interoperability with three data protocol that is coap, mqtt and websocket. From the results of testing developed middleware eligible interoperability.